Edukasi Teknologi Digital dan Energi Terbarukan sebagai Strategi Penguatan Kapasitas Komunitas Peduli Waduk Jlantah Menuju Pariwisata dan UMKM Berkelanjutan di Karanganyar - Ramadhian Agus Triono Sudalyo; Tri Irianto Tjendrowasono; Sukoco Sukoco; Agus Rianto; Abdillah Baradja; Jani Kusanti; Bayu Mukti; Noor Abdul Haris; Frido Oktaviandre (Universitas Teuku Umar, 2026)
This Community Service (PkM) activity aims to enhance the capacity of the Komunitas Peduli Waduk (KPW) at Jlantah Reservoir, Jatiyoso District, Karanganyar Regency, through digital technology education and renewable energy utilization strategies. The activity was held on March 20, 2025 using a Forum Group Discussion (FGD) method, facilitated by the Surakarta River Basin Authority (BBWS), involving 35 participants from Karangsari and Tlobo Villages. Three main topics were delivered: (1) the use of digital technology for tourism promotion and MSME development via social media, websites, and applications; (2) an introduction to renewable energy power generation including micro-hydro and floating solar power plants; and (3) IoT-based water and soil resource monitoring using ESP32 microcontrollers. Results indicated high participant enthusiasm for technology adoption and a clear need for follow-up technical training to build independent community capacity. The activity successfully fostered multi-stakeholder collaboration among academics, the local community, village government, and BBWS Surakarta toward sustainable development of the Jlantah Reservoir area.